Performance management : measure and improve the effectiveness of your employees - Luecke, Richard.; Hall, Brian J. (Harvard business essentials series., 2006)
'Performance Management' will help managers use informal performance assessments and feedback as part of their regular interactions with employees. Readers will learn to prepare for a formal performance meeting with a direct report, document a performance meeting, and create a development plan with the employee.